15–40 GHz wideband CMOS mixer. Issue 24 (1st November 2013) - Cao, Jia; Li, Zhiqun; Li, Qin; Wang, Zhigong
Abstract : A wideband double‐balanced mixer using 90 nm CMOS technology is demonstrated. The DC current paths of the transconductance stage and the switch stage are separated individually by an integrated transformer balun. The primary coil is absorbed in the DC path of transconductance and functions as an inductive load. Simultaneously, the secondary coils perform as a current source of the switch stage. The transconductance employs a common gate amplifier together with the gate‐inductive gain‐peaking technique for providing a wideband input matching and extending the operating bandwidth. The fabricated mixer operates from 15 to 40 GHz with around 5 dB conversion gain, matches to 50 Ω over the full band and only takes up 0.39 mm 2 .